2015
DOI: 10.15226/2471-6529/1/1/00103
|View full text |Cite
|
Sign up to set email alerts
|

Incivility and Student and Faculty Relationships: Implications for Revising Mentorship Programs for Nurse Educators

Abstract: Negative relationships between students and educators are faculty becoming a focus in higher education, this is due in part to the impact on student learning [1,2]. Emerging evidence also reveals that these poor relationships in academic environments are often the cause of educator attrition, [3,4] and nurse educators who experience these deteriorating relationships have an increased likelihood of leaving their employment or nursing altogether [5][6][7][8]. In order to better understand student and nurse educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, discrepancies between student and faculty perceptions of bullying can make it difficult for faculty members to recognize bullying and understand their victims. Therefore, it is essential to conduct studies on teacher perceptions of those who are bullied, those who bully, and the associated risk factors 20,42 . Moreover, Qutishat 14 and Seibel and Fehr 2 identified the factors that increase bullying tendencies among faculty members: A lack of effective communication skills, an inability to manage detected cases of bullying, and a lack of essential skills such as the ability to provide feedback in a nonthreatening manner.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, discrepancies between student and faculty perceptions of bullying can make it difficult for faculty members to recognize bullying and understand their victims. Therefore, it is essential to conduct studies on teacher perceptions of those who are bullied, those who bully, and the associated risk factors 20,42 . Moreover, Qutishat 14 and Seibel and Fehr 2 identified the factors that increase bullying tendencies among faculty members: A lack of effective communication skills, an inability to manage detected cases of bullying, and a lack of essential skills such as the ability to provide feedback in a nonthreatening manner.…”
Section: Discussionmentioning
confidence: 99%
“…While some literature suggests that upward or subordinate bullying is on the rise, [9,59] the sense that students are vulnerable simply by being in the learning role remains the dominant view. This puts the onus on faculty members to create safe and inviting learning environments, whether in the classroom or at clinical sites.…”
Section: Power Dynamics: "They Can Crush You"mentioning
confidence: 99%
“…This puts the onus on faculty members to create safe and inviting learning environments, whether in the classroom or at clinical sites. Diekelman (as cited in Beck [59] ) found that "students were so overwhelmed by all the things they needed to know in their nursing education that it was challenging for them to have a meaningful relationship with faculty that focused on learning" (p. 3). Acknowledging this reality, faculty need to continually be student-centered; bring the focus back to learning, alleviate student anxieties, and acknowledge positive student choices and decision-making.…”
Section: Power Dynamics: "They Can Crush You"mentioning
confidence: 99%
“…The use of power by educators to cover up subject incompetence by acting in an aloof manner, not answering thought-provoking questions, discouraging critical discussions, using ineffective didactic facilitation skills and sending a message that learners are a burden, disturbs learners (Beck, 2015). This goes against the grain of good teaching where learners are treated with dignity and where mutual respect and appropriate boundaries are observed (Gibson et al, 2013;Knepp, 2012).…”
Section: Theme 3: Defence Mechanismmentioning
confidence: 99%
“…This goes against the grain of good teaching where learners are treated with dignity and where mutual respect and appropriate boundaries are observed (Gibson et al, 2013;Knepp, 2012). The inappropriate behaviour that nurse educators display due to job dissatisfaction and their failure to cope because they have inadequate subject KSE hinders the construction of a trusting, mutually respectful learner-nurse educator relationship that is vital for meaningful learning (Beck, 2015;Du Plessis et al, 2015).…”
Section: Theme 3: Defence Mechanismmentioning
confidence: 99%